MicroRNAs and cataracts: correlation among let-7 expression, age and the severity of lens opacity. Issue 5 (14th February 2012) - Peng, Chi-Hsien; Liu, Jorn-Hon; Woung, Lin-Chung; Lin, Tzu-Jung; Chiou, Shih-Hwa; Tseng, Po-Chen; Du, Wen-Yuan; Cheng, Cheng-Kuo; Hu, Chao-Chien; Chien, Ke-Hung; Chen, Shih-Jen
Abstract : Background: Let-7 microRNA is an important regulator of cellular ageing and tissue senescence. The objective of this study is to evaluate the expression of let-7a/let-7b/let-7c microRNAs in human age-related cataracts. Aim: To evaluate the correlation among the severity of lens opacity, the level of let-7a/let-7b/let-7c microRNA expression and patient age in the context of age-related cataracts. Methods: The authors evaluated the mRNA level of let-7a/let-7b/let-7c microRNA in lens epithelia obtained from 174 eyes with age-related cataracts. The authors also recorded the patient age and the severity of lens opacity as classified according to the modified version of the Lens Opacities Classification System version III. Results: Let-7b microRNA expression was demonstrated to be positively associated with patient age ( R =0.472; p<0.001). A positive correlation was also observed between higher N, C and P cataract scores and higher expression of let-7b microRNA in patients with age-related cataracts (p<0.001). However, no significant correlation was observed between the let-7a and let-7c microRNA expression levels and either the severity of lens opacity or the patient age. Conclusion: These findings suggest that microRNAs play a role in age-related cataracts. A local let-7b microRNA increase may represent a risk factor in the formation of age-related cataracts.